The Effect of Non-Excusable Delay Factors on The Completion of Building Construction Projects - Alvin Dunaufal; I Ketut Sucita; Jonathan Saputra (Logic : Jurnal Rancang Bangun dan Teknologi, 2023)
A problem that often occurs in construction projects is the delay in the implementation process. Various factors cause the delay, but in developing countries such as Indonesia, the dominant delay occurs because the implementing contractor causes it for unforgivable reasons (non-excusable delay). This study aims to determine the influence of the non-excusable delay parameter and the relationship between these factors. The research is quantitative with data collection techniques in the form of unstructured interviews, field observations, and surveys using research questionnaires with the number of respondents obtained as many as 33 people consisting of the owner, construction management consultant, quantity surveyor consultant, and ends with confirmation of the results. Research on the implementing contractor. Data analysis was performed using multiple linear regression analysis. The test results of multiple linear regression analysis show that the non-excusable delay factor can significantly affect the completion of construction projects. The influence of each element is 0.434 units for the lack of contractor competence, 0.067 units for inappropriate implementation planning, and -0.097 for inefficient field management units. And simultaneously, these three factors can significantly increase the project delay value index.